The Role of Democratic Leadership Communication towards Organizational Performance: The Case Study of a Sri Lankan Public Hospital - Kaluarachchi, K.A.S.P. (My University, 2012)
Renewed calls for understanding the nature of democratic leadership and its role in democratic movements in organizations are made by Gastil (1994). For the author, the existing definitions of democratic leadership are inconsistent and inadequate. As defined by the author, democratic leadership is “conceptually distinct from positions of authority; rather, it is defined as the performance of three functions: distributing responsibility among the membership, empowering group members, and aiding the group’s decision-making process” (p.953). For Gastil, many, most, or all members of a group are served by these functions in order to exchange the roles of leader and follower. Moreover, a limited number of practical and moral considerations are identified by the author in assessing the appropriateness of the democratic leadership model for different groups. Since leadership plays a pivotal role in democratic movements in organizations, understanding the nature of democratic leadership is essential. Also, little research, so far, has defined democratic leadership within the context of democratic movements in organizations. The leadership literature has paid no or little attention to democratic leadership in such movements, focusing on democratic leadership within small groups and organizations (Choi, 2007). Choi emphasizes that although the available literature on leadership has underlined some characteristics of democratic leadership, it has ignored other demonstrated characteristics of democratic leadership for achieving democratic values on behalf of democratic movements in organizations. Moreover, Gastil (1994) argues that “the absence of a clear definition may have also contributed to the decreased amount of research on democratic leadership” (p. 956). The limited number of empirical studies on democratic leadership to examine the aspect of democratic leadership and its role in democratic movements in organizations provides the opportunity to do fresh research on the topic, in particular to study the aspect of democratic organizational leadership’s role in the enhancement of organizational performance. When it comes to the Sri Lankan context, no or few past empirical studies have used the aspect of democratic organizational leadership to investigate its backing up of democratic movements such as the enhancement of organizational performance of Sri Lankan organizations. Therefore, this research was motivated to study the aspect of democratic leadership and its contribution to the enhancement of organizational performance in the Sri Lankan context. In particular, the intended aim or purpose of the research was further specified: to study how the enhancement of organizational performance of a Sri Lankan public hospital has been accomplished due to its democratic leadership communication over time. The investigation was theorized using the “ideal type communication principle” of Habermas (1984, 1987).